Perspectives of Environmental Awareness in University Students - Vilcapoma-Malpartida, Pedro-Manuel; Vilcañaupa-Toralava, Geovana-Miriam; Huamán-Romaní, Yersi-Luis; Huaraca-Aparco , Rosa; Aragón-Navarrete , Ruth-Nátaly; Machaca-Mamani, Julio-César (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
To practice environmental awareness is to leave a legacy for a better world and this will be achieved with the support of students and society, for this reason the main objective of this research is to describe and analyze the perspectives of environmental awareness in university students, for which the methodology of quantitative approach is used, correlational between its elements and predictive, in which 1324 university students who responded to a survey of 17 questions divided into four dimensions participated.